Computational Platform for the Educational Model based on the Cloud Paradigm - Aguilar Castro, J. (2015)
The Department of Computer Science at the University of Los Andes has proposed a new curriculum model based on the profile defined by ACM/IEEE, and a pedagogical model based on the "learning by doing" paradigm, in order to ensure a process of self-formation of the student. The knowledge management and the learning process are based on the concept of clouds. The new educational model is based on three clouds: a) the self-formation cloud which is composed of everything related to the student's education (curriculum, etc.); b) the learning paradigm cloud which is related to the paradigms, strategies, forms of assessment, and learning tools; and c) the knowledge sources cloud which is composed of all existing knowledge in the world, in all its forms, from all possible sources. To give support to the educational model, a web platform based on Service Oriented Architecture (SOA) is proposed in this work. The system consists of three management layers; each one manages each one of the clouds described above. The implementation of each layer is made as web services. Each layer has its own data structure defined like ontology. This is called Extended Database, which also has the ability to support processes of reasoning over it.